Strength and conditioning practices of Iran wrestling league strength and conditioning coaches - Jamshidi, F. S.; Mirzeai, B.; Damirchi, A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose : The purpose of this study describes the results of a survey of the practices of Iranian Wrestling League strength and conditioning (IWL S&C) coaches.